METHODS OF COMMUNICATION IN THE FAMILY: (HISTORY ABOUT COMMUNICATION BETWEEN CHILDREN AND ETHICAL CULTIVATION FOR CHILDREN) THE CHILDREN) - Fandi Alfiansyah Siregar; Aisyah Rambe; Rafiqah Yusna Siregar (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2023)
ABSTRACT  The study aims to examine how the communication between children within the family relates to the cultivation of morals for them. The theory considered relevant and used in this study is Family Communication. In contrast, the research method applied in this research using a qualitative descriptive approach. This research also uses content analysis techniques from the group of hadiths that the researchers use to then be analyzed with the focus of family communication research in order to implant ethics for children. The data collection technique is carried out in two stages, namely the study of libraries and documentation. The results of research show that the ethics of communication in Islam are built on the guidance that is indicated by the Qur’an and the Sunnah. Islam teaches to communicate with full civilization, respect, respect for the person who speaks, and so on. When speaking to others, Islam gives a clear foundation on how to speak. When ethics is associated with family communication, then ethics becomes the basis of policy in family communication. Ethics provides a moral foundation in building a susila system against all attitudes and behaviors of individuals or groups in communication. Thus, without ethics communication is judged unethical. The moral behavior of children is reflected in the ethics of communication from their families.The morality of children depends on communication within the family. Keywords: Family Communication, Hadith and Morality